Vegetation Structure of The Sumatran Rhino Habitat In The Kapi, Leuser Ecosystem Area, Aceh Province - Rahmadetiassani, Afifi; Darnaedi, Dedy; Samedi, Samedi; Putra, Rudi H.; Khan, Latif; Hanum, Cut Maila (Journal of Tropical Biodiversity, 2025)
The Sumatran rhino (Dicerorhinus sumatrensis) is one of the most critically endangered large mammals, with fewer than 100 individuals remaining. Habitat quality plays a vital role in ensuring its survival and reproduction. The Kapi area within the Leuser Ecosystem Area (LEA) is considered one of the potential remaining habitats for this species, yet data on its vegetation structure is limited. This study aimed to analyze and describe vegetation conditions in Kapi by examining species composition, similarity, diversity, evenness, and importance value index (IVI). Vegetation data were collected from October to December 2021 using randomly distributed sample plots across all vegetation strata. A total of 98 plant species from 37 families and 7,394 individual plants were recorded, comprising 67 species in the tree stratum, 43 species in the pole stratum, 42 species in the sapling stratum, and 43 species in the seedling stratum. Species similarity was highest between sapling and pole strata (63.53%) and lowest between sapling and tree strata (45.87%). Seventy-nine plant species from 29 families were identified as rhino food plants. Diversity was highest in the tree stratum (H’=3.32) and lowest in the seedling stratum (H’=2.88). Evenness peaked in the pole stratum (E=0.83) and was lowest in the seedling stratum (E=0.76). IVI analysis indicated different dominant species in each stratum.